Case-mix adjustment to compare colonoscopy performance between endoscopy centers: a nationwide registry study - Nass, Karlijn J.; van der Vlugt, Manon; Elfrink, Arthur K. E.; van den Brand, Crispijn L.; Wilschut, Janneke A.; Fockens, Paul; Dekker, Evelien; Wouters, Michel W. J. M.; in collaboration with the Dutch Gastrointestinal Endoscopy Audit group (Endoscopy, 2021)
Background Nonmodifiable patient and endoscopy characteristics might influence colonoscopy performance. Differences in these so-called case-mix factors are likely to exist between endoscopy centers. This study aimed to examine the importance of case-mix adjustment when comparing performance between endoscopy centers.Methods Prospectively collected data recorded in the Dutch national colonoscopy registry between 2016 and 2019 were retrospectively analyzed. Cecal intubation rate (CIR) and adequate bowel preparation rate (ABPR) were analyzed. Additionally, polyp detection rate (PDR) was studied in screening colonoscopies following a positive fecal immunochemical test (FIT). Variation in case-mix factors between endoscopy centers and expected outcomes for each performance measure were calculated per endoscopy center based on case-mix factors (sex, age, American Society of Anesthesiologist [ASA] score, indication) using multivariable logistic regression.Results 363 840 colonoscopies were included from 51 endoscopy centers. Mean percentages per endoscopy center were significantly different for age > 65 years, male patients, ASA ≥ III, and diagnostic colonoscopies (all P < 0.001). In the FIT-positive screening population, significant differences were observed between endoscopy centers for age > 65 years, male patients, and ASA ≥ III (all P ≤ 0.001). The expected CIR, ABPR, and PDR ranged from 95.0 % to 96.9 %, from 93.6 % to 96.4 %, and from 76.2 % to 79.1 %, respectively. Age, sex, ASA classification, and indication were significant case-mix factors for CIR and ABPR. In the FIT-positive screening population, age, sex, and ASA classification were significant case-mix factors for PDR.Conclusion Our findings emphasize the importance of considering case-mix adjustment when comparing colonoscopy performance measures between endoscopy centers.